ANALYSIS OF MARKETING COMMUNICATION STRATEGIES IN INCREASING BRAND AWARENESS - Shella Septiani; Nurul Mardiyyah Pratiwi; M Furqon; Miftahul Jannah; A Sazili (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
Changes in the lifestyle of the millennial generation who now like to drink coffee with friends have an impact on the business economy with the emergence of new coffee shops in Indonesia with a variety of names and products. Marketing communication strategy is important for companies. To survive in the market, companies need to organize effective and appropriate corporate strategies. This research aims to find out the strategy. The The locus of this research at Kopi Janji Jiwa Opi Mall Palembang Branch Jl. Governor H. A Bastari, Sungai Kedukan, South Sumatra The sample of this study amounted to 50 respondents. The type of research used in this research is descriptive qualitative using descriptive statistical data analysis techniques and interactive analysis techniques. The results showed that Kopi Janji Jiwa maximizes marketing communication strategies through digital marketing strategies by carrying out the PENCILS concept (Publications, Events, News, Community Involvement, Identity Media, Lobbying, and Social Investment) and digital media strategies. In the brand awareness pyramid level, Kopi Janji Jiwa has not reached the top of mind level but Brand Recall.